2014
DOI: 10.1007/s00449-014-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofilm formation on the performance of microbial fuel cell for the treatment of palm oil mill effluent

Abstract: Anode biofilm is a crucial component in microbial fuel cells (MFCs) for electrogenesis. Better knowledge about the biofilm development process on electrode surface is believed to improve MFC performance. In this study, double-chamber microbial fuel cell was operated with diluted POME (initial COD = 1,000 mg L(-1)) and polyacrylonitrile carbon felt was used as electrode. The maximum power density, COD removal efficiency and Coulombic efficiency were found as 22 mW m(-2), 70 and 24 %, respectively. FTIR and TGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…It is interesting to note that the anode charge transfer resistance (R ct ) after 14 days of continuous microbial growth was more or less same as that on day 7. Our previous results [20] showed that stable biofilm can be formed within even 7 days of MFC operation and these results support the same. A biofilm formed on the electrode surface during the MFC operation with anaerobic sludge, was usually enriched with electrochemically active bacteria [13] which might reduce the charge transfer resistance.…”
Section: Ftir Analysis Of the Biofilmsupporting
confidence: 81%
See 3 more Smart Citations
“…It is interesting to note that the anode charge transfer resistance (R ct ) after 14 days of continuous microbial growth was more or less same as that on day 7. Our previous results [20] showed that stable biofilm can be formed within even 7 days of MFC operation and these results support the same. A biofilm formed on the electrode surface during the MFC operation with anaerobic sludge, was usually enriched with electrochemically active bacteria [13] which might reduce the charge transfer resistance.…”
Section: Ftir Analysis Of the Biofilmsupporting
confidence: 81%
“…A biofilm formed on the electrode surface during the MFC operation with anaerobic sludge, was usually enriched with electrochemically active bacteria [13] which might reduce the charge transfer resistance. As a result, the development of the microbial biofilm on the anode was found to be decreased the polarization resistance and facilitates the kinetics of the electrochemical reactions [20]. This investigation confirmed the fact that the anode charge transfer resistance is strongly influenced by the microbes growing on the anode surface.…”
Section: Ftir Analysis Of the Biofilmsupporting
confidence: 76%
See 2 more Smart Citations
“…The chamber material was made from an acrylic sheet, and carbon felt was selected as the electrode material. As carbon felt has a high porosity and large surface area, and is conducive to microbial growth [13], adhesion, and reduction of activation impedance [14], it was considered the best choice. The carbon felt was pretreated before the study by being soaked and heated at a condition of 90°C with a volume of 10% hydrogen peroxide solution for 3 h, and then air-dried so as to increase the adhesion and proliferation of microbes [15].The different chambers of the SMFCs were manufactured for particular experimental requirements.…”
Section: Model Of Experimentsmentioning
confidence: 99%